CANE FARMERS COMMUNITY PARTNERSHIP PATTERN WITH PT. PG. GORONTALO - Anas Jusuf; Amir Halid; Muhammad Amir Arham (State University of Gorontalo, 2019)
The study aims to (1) Describe the perception of sugar cane farmers in the district was on a partnership with PT. PG. Gorontalo farmers; (2) Describe the factors that influence the success of the partnership program sugar cane farmers in the district was by PT. PG. Gorontalo; (3) Analyze the contribution of sugar cane farmer partnership with PT. PG. Gorontalo to the income of farmers in the district was. This research is quantitative. Sources of data in this study are primary data from questionnaires to farmers. Data analysis technique used is descriptive analysis, regression and simple regression. These results indicate that (1) The partnership pattern obtained and applied to partnerships sugar cane farmers in the district was by PT. PG. Tolangohula namely Gorontalo Province Operational Cooperation patterns Agribusiness (KOA). Farmer partnerships to provide benefits to growers of sugar cane but still less than optimal on the issue of determining the selling price of sugar cane is not appropriate and farmers' rights and obligations of the partner company of farmers not fulfilled in accordance with the terms and agreements. (2) The results of multiple regression analysis about factors that affect the success of the partnership of farmers found that internal factors, external factors, the characteristics of partnership, participation of farmers and supporting components of the partnership jointly significant effect on the success of the partnership program sugar cane growers of the people in the district was the value of the determinant of 63.30%, while it partially only variable that does not pick internal factors have a significant effect. (3) Partnerships sugar cane farmers in the district was by PT. PG. Gorontalo positive and significant impact on people's income taboo sugar cane farmers in the district was the positive benefit contribution rate of 0.268 or by 26.8%. This shows that the partnership is very beneficial for farmers' incomes but its implementation still need to be addressed in order to provide a greater contribution to the income of farmers folk taboo.